Dynamics of the Management and Implementation of Colonial Health Policy at Pandeglang Hospital (1925–1935) - Desma Febrianti; Rikza Fauzan; Muhammad Anggie Farizqi Prasadana (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This article examines the management dynamics of Pandeglang Hospital from 1925 to 1935 in the context of changing colonial health policy in the Dutch East Indies. The study applies the historical method through heuristics, source criticism, interpretation, and historiography using colonial health reports, government regulations, and supporting literature. The findings show that institutional change from a military-oriented system to civilian health services shaped administrative standardization, patient classification, subsidy mechanisms, and medical supervision at Pandeglang Hospital. The hospital became important in handling endemic disease, serving as a regional referral center, and strengthening local medical personnel, yet its impact on mortality remained limited because poverty, poor sanitation, and the global economic crisis constrained colonial medical intervention. This case highlights how colonial health policy was implemented unevenly at the local level.